STRENGTHENING INDONESIA’S ROLE IN INDIAN OCEAN THROUGH INDIAN OCEAN RIM ASSOCIATION CHAIRMANSHIP IN 2015-2017 - Setiyanto, Ari (Jurnal Pertahanan dan Bela Negara, 2018)
Indonesian government concerned to determine the future of the Pacific and Indian Ocean Region through new vision as the world maritime fulcrum. The elected President, Joko Widodo realized the importance to strengthen the priority in maritime sector. Expanding globalization and growing needs of energy security leads Indian Ocean region as an important area for the global security. Regionalism has implications for both security and development in a region. Significant growth in Indian Ocean region urges a cooperation approach between littoral countries located around the Indian Ocean and lead the establishment of Indian Ocean Rim Association (IORA). As Indonesia will be a chairman in IORA by the third quarter of 2015, Indonesia can play an important role and influence the region with its chairmanship in IORA, both in terms of economy and security. Indonesia could develop a comprehensive maritime cooperation through the IORA. The cooperation will lead to acomplishment of the Indonesia’s national interests. On the other side, the potential trade volume in the Indian Ocean region cannot be reached because of limited maritime infrastructure that facilitate the current trade. IORA should develop a master plan or blueprint on connectivity that will provide the infrastructure development agenda with the Public-Private Partnership to accelerate the infrastructure development. By this situation, the development of maritime infrastructure can be a double advantage for Indonesia because it will connect APEC and IORA. The important things to consider in terms of security is a potential threat both in security and defense if the government decided to open and build a deep seaport in Western Sumatera and Java Island.It is important to evaluate the potential threats and challenges if Indonesia wants to be a fulcrum ofworld maritime activity. Keywords: IORA, diplomacy, maritime security, regional integration, maritime fulcrum, regionalism